From Poetry to Narration with Mazaher Mosaffa: Taking a look at'The Proceedings' (Noskhe-ye Eghdam) - Hamidreza Tavakkoli (مطالعات زبانی و بلاغی)
Mazaher Mossafa’s poems or continuant couplets  which are collected in ‘The Proceedings’ (Noskhe-ye Eghdam) are noteworthy from different perspectives: the interaction between the poetic side and narrative aspect; the romantic color; story-telling and the transition of memories, especially childhood ones; parading personal experiences and describing the details; climatic coloring and the reflection of the folklore, passing through the most personal agonies to national distress or even the historical injuries of Iran; the role of association in altering atmospheres; weird conversations, from addressing a mountain to addressing a mirror and even to addressing his two year old brother passed away before the birth of the poet but granted his name and memory and birth  certificate to him. This piece of writing is an endeavor to pinpoint these perspectives, though in short, emphasizing the prominent cases, particularly focusing on the status of this distinct collection in order to recognize the unnoticed facets of the poet.